Property Tax Decentralisation Program, Punjab, Pakistan : Time Bound Action Plan - World Bank (Washington, DC, 2013)
This document is part two of the blueprint and represents an expression of the organization, process and solution design for all areas covered in the vision of a modern, fit for purpose property tax department. The scope of this document sets out a time bound action plan that covers both the high level design of the new organization as well as the program to deliver the specific operation. If the proposals in the blue print were to be adopted by the provincial government it is believe that, based on our experience, the reform process will take a minimum of five years. The action plan is, therefore, based on a five-year period, this can, of course, be adapted to take account of local circumstances. It has to be said that many of the issues identified in the inception report, the diagnostic report and the blueprint have been identified previously in various consultancy reports and were recognized by the provincial government in the Medium Term Policy Framework but little action has ensued.